2014
DOI: 10.1016/j.jagp.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Making and Executing Decisions for Safe and Independent Living (MED-SAIL): Development and Validation of a Brief Screening Tool

Abstract: Objectives Older adults prefer to remain in their own homes for as long as possible. The purpose of this article is to describe the development and preliminary validation of Making and Executing Decisions for Safe and Independent Living (MED-SAIL), a brief screening tool for capacity to live safely and independently in the community. Design Prospective preliminary validation study. Setting Outpatient geriatrics clinic located in a community-based hospital. Participants Forty-nine community-dwelling older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The articles identified in the literature search provided some information on assessment tools that could be used by social workers. These included generalized assessment tools ( Craig et al, 2015 ), a screening tool to assess safety of independent living ( Mills et al, 2014 ), integrated care assessment tools ( Taylor, 2012 ; Warburton et al, 2015 ), a spiritual assessment tool ( Harrington, 2016 ), and comprehensive assessments of older people with complex needs ( Australian Government, 2018 ; Lambert et al, 2009 ; Sansoni et al, 2012 ), shown in Table 1 . There was limited access to the tools referred to in the publications, and included questions or domains were generally not provided.…”
Section: Resultsmentioning
confidence: 99%
“…The articles identified in the literature search provided some information on assessment tools that could be used by social workers. These included generalized assessment tools ( Craig et al, 2015 ), a screening tool to assess safety of independent living ( Mills et al, 2014 ), integrated care assessment tools ( Taylor, 2012 ; Warburton et al, 2015 ), a spiritual assessment tool ( Harrington, 2016 ), and comprehensive assessments of older people with complex needs ( Australian Government, 2018 ; Lambert et al, 2009 ; Sansoni et al, 2012 ), shown in Table 1 . There was limited access to the tools referred to in the publications, and included questions or domains were generally not provided.…”
Section: Resultsmentioning
confidence: 99%
“…Though legal definitions of DMC vary internationally, most legislation and literature pertaining to DMC generally define DMC for any domain in terms of four widely accepted criteria: understanding, appreciation, reasoning and expression of choice (Grisso & Appelbaum, 1998). In relation to DMC for IL, the majority of publications in this review advocate for a functional approach to DMC assessment, incorporating these four dimensions, namely, the assessment of the person's abilities to understand relevant information about the situation, appreciate how relevant information applies to oneself in the situation, engage in rational deliberation about available options and to make and communicate a choice (Brindle & Holmes, 2005;Carrese, 2006;Clionsky et al, 2016;Cooney et al, 2004;Darzins, 2010;Emmett et al, 2013;Hughes et al, 2015;Jayes et al, 2017;Mackenzie et al, 2008;Mills et al, 2014;Naik, 2017a;Naik, Lai, et al, 2008;Stewart et al, 2005;Usher & Stapleton, 2020a).…”
Section: Theme 1: Functional Approach To Dmc Assessment For Ilmentioning
confidence: 99%
“…Capacity for IL lies at the confluence of function, cognition and judgment (Mills et al, 2014). Unlike other domains of DMC, such as DMC for medical consent, which is largely a cognitive task, DMC for IL is a broad domain encompassing multiple everyday life functions and skills (Naik, Teal, et al, 2008).…”
Section: Theme 3: Components Of Dmc Assessment For Ilmentioning
confidence: 99%
See 1 more Smart Citation
“…DMC assessments regarding independent living must address function, cognition and judgment as overlapping domains (Mills et al, 2014). Therefore, determining if an older adult can make and execute decisions to live safely at home presents a complicated challenge to health-care professionals (Skelton et al, 2010) and the concept of DMC for independent living is frequently misunderstood.…”
Section: Assessment Of Dmc For Independent Livingmentioning
confidence: 99%